The perceptions of Botswana agricultural science teachers towards their in-service professional development: an exploratory study of the central region - Mabusa, Kgomotso (2016)
This study relates to the reforms by the Education Ministry in Botswana of decentralising the coordination of teachers’ In-service Professional Development (IPD) to the Regional Offices with the overall aim of improving students’ academic performance (Republic of Botswana, 2006). In the absence of other research data, the study aims to understand how secondary school teachers of agriculture in Botswana perceive their IPD. The study endeavours to identify gaps in current IPD provision and make recommendations to guide IPD policy reforms at regional level.